Indices relation and statistical probability analysis of physical and mechanical performance of asphalt mixtures - Rui Guo; Fei zhou; Tengfei Nian (Case Studies in Construction Materials, 2022)
Rutting deformation is one of the most prominent diseases in asphalt pavement’s early damage. In this paper, it analyzes the relation and their distribution law between Marshall stability and the physical and mechanical indices of asphalt mixtures based upon a correlation analysis and statistical principles, which is to find the reasonable range of rutting performance design parameters of asphalt pavement. The results showed that the asphalt mixture’s stability increased with the increase in bulk volume relative density and asphalt saturation, but decreased with the increase in the percent of air-voids and the voids in the mineral aggregate. The optimal fitting function of bulk volume relative density and asphalt saturation for AC-13 asphalt mixture follows a Weibull distribution, that of Marshall stability and air-voids follows a Gamma distribution, and that of percent voids in the mineral aggregate and flow value follows a Lognormal distribution. For a GAM-16 asphalt mixture, the optimal fitting function of bulk volume relative density and Marshall stability follows the Weibull distribution, the optimal fitting function of air-voids follows a Gamma distribution, that of flow value and percent voids in the mineral aggregate follows a Lognormal distribution, and asphalt saturation follows a Normal distribution. It is recommended that AC-13 asphalt mixtures’bulk volume relative density ranges from 2.27～2.38 g·cm3, the air-voids ranges from 3.4～6.0%, and GAM-16 asphalt mixtures’bulk volume relative density ranges from 2.29～2.37 g·cm3, the voids in mineral aggregate ranges from 17～18.17%, the asphalt saturation ranges from 75～82.13%, which can provide a reference for in-depth understanding of the deformation characteristics and construction of highways’ pavement in similar areas.